Remediation of nitrate contaminated groundwater using a simulated PRB system with an La–CTAC–modified biochar filler - Li, Sen; Wu, Yong; Nie, Fuyu; Tu, Weiguo; Li, Xueling; Luo, Xuemei; Luo, Yong; Fan, Hua; Song, Tao (Frontiers in Environmental Science, 2022)
In the present study, the Erigeron canadensis L., a typical invasive plant in Southwest China, was utilized as the raw material to prepare original biochar (ECL), a rare earth element La–modified biochar (La–ECL), and a rare earth element La coupling cationic surfactant (cetyltrimethylammonium chloride (CTAC))–modified biochar (La/CTAC–ECL). These materials were then added to simulated permeable reactive barriers (PRBs) and their nitrate (NO3–) contaminant remediation performances were evaluated in groundwater. The results show that the breakthrough time for NO3– in a simulated PRB column increases as the concentration of the influent NO3– and the flow rate decreases, whereas with the increases of filler particle size and the height of the filler in the column initially increases, and then decreases. Considering an initial NO3– concentration of 50 mg L−1, and a filler particle size range of 0.8–1.2 mm, the maximum adsorption capacity of the La/CTAC–ECL column for NO3– is 18.99 mg g−1 for a filler column height of 10 cm and an influent flow rate of 15 mL min−1. The maximum quantity of adsorbed NO3– of 372.80 mg is obtained using a filler column height of 15 cm and an influent flow rate of 10 mL min−1. The Thomas and Yoon–Nelson models accurately predict the breakthrough of NO3– in groundwater in the simulated PRB column under different conditions, and the results are consistent with those from dynamic NO3– adsorption experiments. TEM, XRD, FTIR, and XPS analyses demonstrate that the modification using the La and CTAC improves the surface structure, porosity, permeability, and configuration of functional groups of the biochar. The mechanisms of NO3– removal from groundwater using the La/CTAC–ECL include pore filling, surface adsorption, ion exchange, and electrostatic adsorption. The composite La/CTAC–ECL exhibits a superior potential for the remediation of NO3– contaminated groundwater.